THE EFFECT OF PROFITABILITY, LIQUIDITY, LEVERAGE, SALES GROWTH ON FINANCIAL DISTRESS IN CONSUMER AND NON-CONSUMER CYCLICALS COMPANIES LISTED ON THE IDX DURING THE 2019-2021 - Friska, Gracelia; Pudjolaksono, Drs. Eko (jfpublisher, 2023)
The ability of a company to compete is determined by the company’s performance. If there is a lack of effectiveness in the company’s performance, then company leaders can take the right action to ensure that things become more efficient. Moreover, performance measurement is closely related to the company’s financial condition. Every company should create and use financial reports in the process of managing the company’s finances. Therefore, this research is needed to find out the effect of profitability, liquidity, leverage, sales growth on financial distress in consumer and non-consumer cyclicals companies listed on the IDX during the 2019-2021. The sampling method used in this research is nonprobability sampling by applying purposive sampling technique. The sample used in this research consists of trading companies listed on the Indonesia Stock Exchange (IDX) during the 2019-2021 that are engaged in buying and selling activities without production. The results of this research indicate that (1) the profitability ratio measured using Return on Asset has a positive effect on financial distress; (2) the profitability ratio measured using Return on Equity has a negative effect on financial distress; (3) the liquidity ratio measured using the Current Ratio has no effect on financial distress; (4) the leverage ratio measured using the Debt Equity Ratio has an effect on financial distress; and (5) the sales growth ratio has no effect on financial distress in trading sector companies listed on the IDX during 2019-2021.